Spin excitation spectrum of high-temperature cuprate superconductors from finite cluster simulations - Lychkovskiy, Oleg; Fine, Boris V. (Journal of physics. Condensed matter, 2018)
A cluster of spins 1/2 of a finite size can be regarded as a basic building block of a spin texture in high-temperature cuprate superconductors. If this texture has the character of a network of weakly coupled spin clusters, then spin excitation spectra of finite clusters are expected to capture the principal features of the experimental spin response. We calculate spin excitation spectra of several clusters of spins 1/2 coupled by Heisenberg interaction. We find that the calculated spectra exhibit a high degree of variability representative of the actual phenomenology of cuprates, while, at the same time, reproducing a number of important features of the experimentally measured spin response. Among such features are the spin gap, the broad peak around ≃ (40-70) meV and the sharp peak at zero frequency. The latter feature emerges due to transitions inside the ground-state multiplet of the so-called ‘uncompensated’ clusters with an odd number of spins.
Gesehen am 30.07.2019